Socialization and Discussion of South Sumatra Coffee with Jack Runners Roastery at Livin' Fest 2025 Palembang - M Arief Rahman; Ferizka Tiara Devani (Jurnal Perjuangan dan Pengabdian Masyarakat : JPPM, 2026)
The community engagement activity conducted at Livin’ Fest 2025 Palembang aimed to introduce the potential of South Sumatra coffee to the broader public through an interactive educational approach. The urgency of this activity lies in the need to improve public literacy regarding local coffee quality, processing techniques, and flavor characteristics that are not yet fully understood by consumers. The objective was to provide comprehensive insights into South Sumatra coffee while creating opportunities for collaboration among industry actors, communities, and educational institutions. The method employed a descriptive qualitative approach through direct observation and discussions with Jack Runners Roastery, involving active interactions between presenters, local coffee practitioners, and festival visitors. The results indicated that material delivery through brewing demonstrations, explanation of coffee profiles, and question-and-answer sessions successfully enhanced participants’ understanding of processing differences, flavor potential, and production challenges. The activity also strengthened public appreciation for local products and supported network expansion among coffee stakeholders. The conclusion highlights that festival-based educational activities can serve as an effective strategy to improve the quality, promotion, and competitiveness of South Sumatra coffee.